2011
DOI: 10.1108/01409171111116295
|View full text |Cite
|
Sign up to set email alerts
|

The effects of firm performance on corporate governance

Abstract: PurposeThe purpose of this paper is to investigate the effects of prior firm performance on board composition and governance structure.Design/methodology/approachA total of 90 companies listed on National Association of Securities Dealers Automated Quotations were used for this study. Hypotheses were tested using both general linear regression and logit regression analyses.FindingsThe results showed that prior negative change in firm performance was significantly related to a decrease in the overall number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
36
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 73 publications
7
36
0
1
Order By: Relevance
“…This is consistent with the results of prior researches that revealed a negative significant association between board independence and Tobin`s Q either in developed countries (Singh & Gaur, 2009;Stanwick & Stanwick, 2010;Switzer & Tangb, 2009;Valenti et al, 2011;Wang & Oliver, 2009) or in developing countries like Mohd (2011) and Khan and Javid (2011). One reasonable explanation for the negative significant association between board independence and Tobin`s is that frequent board meetings do not automatically translate to enhanced firm performance but it may reflect issues in the firm (Jensen, 1993).…”
Section: Regression Results Of Model (Based On Marketing Measure)supporting
confidence: 82%
See 1 more Smart Citation
“…This is consistent with the results of prior researches that revealed a negative significant association between board independence and Tobin`s Q either in developed countries (Singh & Gaur, 2009;Stanwick & Stanwick, 2010;Switzer & Tangb, 2009;Valenti et al, 2011;Wang & Oliver, 2009) or in developing countries like Mohd (2011) and Khan and Javid (2011). One reasonable explanation for the negative significant association between board independence and Tobin`s is that frequent board meetings do not automatically translate to enhanced firm performance but it may reflect issues in the firm (Jensen, 1993).…”
Section: Regression Results Of Model (Based On Marketing Measure)supporting
confidence: 82%
“…Form other side, many researchers have also found that there is a negative relationship between board independence and firm performance in developed countries like Singh & Gaur, 2009;Stanwick & Stanwick, 2010;Switzer & Tangb, 2009;Valenti et al, 2011;Wang & Oliver, 2009). A similar finding is reported in the developing countries in the studies Mohd (2011) and Khan and Javid (2011).…”
Section: Board Composition and Firm Performancesupporting
confidence: 71%
“…In the same vein, in Indonesia, the ownership structure and commissioners have no effect on online financial disclosure; the characteristics of the audit committee are the only factor that increases online financial disclosure (Puspitaningrum & Atmini, 2012). Finally, a reduction in the number of directors is related to poor performance in the United States (Valenti et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…They find that only the third factor affects the outcome, particularly the number of times that the audit committee meets. Finally, Valenti et al (2011) discover that a decrease in the total number of directors and the number of external directors is ijbm.ccsenet.org…”
Section: Ownership Structurementioning
confidence: 99%
“…Alves (2011) reported that empirical results support the predicted nonlinear relationship between board size and earnings management. Prior negative change in firm performance was significantly related to a decrease in the overall number of directors and a decrease in the number of outside directors (Valenti et al, 2011). Kumar and Singh (2013) found a negative relationship of board size to firm value in Indian context.…”
Section: Board Sizementioning
confidence: 99%